2006
DOI: 10.1542/peds.2005-1551
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Maternal Depressive Symptoms and Mothers' Parenting Practices With Young Children: Implications for Pediatric Practice

Abstract: The study findings suggest that concurrent maternal depressive symptoms have stronger relations than earlier depressive symptoms, with mothers not initiating recommended age-appropriate safety and child development practices and also using harsh discipline practices for toddlers. Our findings, however, also suggest that for parenting practices that are likely to be established early in the life of the child, it may be reasonable that mothers with early depressive symptoms may continue to affect use of those pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
148
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 31 publications
10
148
1
1
Order By: Relevance
“…Consistent with previous work indicating that maternal depression negatively impacts parenting and feeding practices (10,15,41) and that unhealthy eating may partially underlie links between maternal depression and children's weight (32) , our study found associations between mothers' depressive symptoms and their children's lower consumption of healthy foods across analysis models. Notably, however, our measure of children's food consumption was predominantly mother-reported, did not assess serving size and had low reliability, which may account for its lack of predictive value for children's weight outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous work indicating that maternal depression negatively impacts parenting and feeding practices (10,15,41) and that unhealthy eating may partially underlie links between maternal depression and children's weight (32) , our study found associations between mothers' depressive symptoms and their children's lower consumption of healthy foods across analysis models. Notably, however, our measure of children's food consumption was predominantly mother-reported, did not assess serving size and had low reliability, which may account for its lack of predictive value for children's weight outcomes.…”
Section: Discussionsupporting
confidence: 90%
“…These mothers also reported more difficulties coping with parenting demands and were more likely to use punitive parenting strategies. Our findings support those of other studies that have examined the association between maternal depressive symptoms and parenting practices from birth to entry into kindergarten (Kavanaugh et al, 2006;McLearn, Minkovitz, Strobino, Marks, & Hou, 2006a, 2006bPaulson & Bazemore, 2010). It highlights the fact that it is not uncommon for parents with young children to report depressive symptoms that affect their ability to carry out critical parenting behaviors central to children's health and wellbeing.…”
Section: Discussionsupporting
confidence: 88%
“…21,29 Moreover, this finding is particularly concerning given that children were only 1 year of age in our study, a developmental stage when children are unlikely to understand the connection between their behavior and subsequent punishment and when spanking is more likely to cause physical injury. 30 Although associations between spanking and maternal depression have been previously reported, 31 this is the first study, to our knowledge, to report an association between spanking and paternal depression. Notably, in a national sample of 499 fathers of children under 3 years of age, Lyons-Ruth et al 32 did not find an association between paternal depressive symptoms and spanking but did report an association between a father's depressive symptoms and his report of "hitting, slapping, or shaking" his child.…”
Section: Figurementioning
confidence: 76%